VoIP and PBX Security and Forensics A Practical Approach - Androulidakis, Iosif I. (SpringerBriefs in Electrical and Computer Engineering,, 2016)
This book begins with an introduction to PBXs (Private Branch Exchanges) and the scene, statistics and involved actors. It discusses confidentiality, integrity and availability threats in PBXs. The author examines the threats and the technical background as well as security and forensics involving PBXs. The purpose of this book is to raise user awareness in regards to security and privacy threats present in PBXs, helping both users and administrators safeguard their systems. The new edition includes a major update and extension to the VoIP sections in addition to updates to forensics.